Gemcitabine-induced haemolytic uraemic syndrome in pancreatic adenocarcinoma. Issue 4 (8th April 2019) - Das, Adarsh; Dean, Andrew; Clay, Tim
Abstract : A woman in her mid-70s with metastatic pancreatic adenocarcinoma presented with fatigue, nausea and bilateral leg swelling, 4 days after an intravenous gemcitabine infusion. Additional examination and laboratory tests showed mild hypertension, low haemoglobin, high lactate dehydrogenase, low platelet count and high serum creatinine. The patient was subsequently diagnosed with haemolytic uraemic syndrome (HUS), and gemcitabine administration was immediately ceased. The patient received a 5-day course of methylprednisolone, with a full recovery being made 10 days after diagnosis. Clinicians should be aware of the rare but serious complication of gemcitabine-induced HUS (GiHUS), as early diagnosis and management, which includes prompt discontinuation of gemcitabine, are crucial in promptly resolving this condition. This case report describes one treatment that can be used for the treatment of GiHUS, while briefly covering some other novel treatments that have been described in other studies.